2020
DOI: 10.1021/acs.jpcc.0c02383
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Nonlinear Optical Properties of 2D Metallic NbS2 in the Near Infrared

Abstract: The understanding of the nonlinear optical (NLO) properties of photonic materials is relevant and necessary for basic studies and technological developments. Among the materials with high optical nonlinearities, layered transition-metal dichalcogenides (LTMDs) have attracted considerable attention from the viewpoint of both synthesis as well as characterization and applications. We report here the third-order NLO properties of one LTMDthe metallic NbS2that was prepared by a modified redox exfoliated method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 42 publications
(72 reference statements)
4
20
0
Order By: Relevance
“…This different stacking leads to different physical properties. In this study, the 2H-NbS 2 phase is present, and this is demonstrated in the TEM and Raman analysis in recent studies …”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…This different stacking leads to different physical properties. In this study, the 2H-NbS 2 phase is present, and this is demonstrated in the TEM and Raman analysis in recent studies …”
Section: Resultssupporting
confidence: 61%
“…It should be noticed that the NLS mechanism was also observed to contribute to the NLT process for the same NbS 2 sample studied by 800 nm optical Z-scan with 100 fs input pulses. 30 ZrTe 2 presents a semimetallic character, as confirmed recently via angle-resolved photoemission spectroscopy (ARPES), 11 besides its topological semimetal character. 31 Figure 6 shows the results for OZ-and PAZ-scans.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…[51] In addition, the two peaks at higher binding energies belonging to NbS 2 nanowires are observed at 207.4 and 210.2 eV, which can be assigned to Nb 5+ 3d 5/2 and Nb 5+ 3d 3/2 of Nb 2 O 5 because of oxidation on the surface. [52,53] Raman spectra for the samples are obtained using a laser with a wave length of 532 nm as the light source. As shown in Figure S4 (Supporting Information), those for sample N-4 exhibit four peaks at 312.4, 333.1, 381.2, and 449.2 cm −1 , which could be the characteristic peaks of NbS 2 corresponding to the E 1 , E 2 , A 1 , and A 2 vibration modes, [30,54] respectively.…”
Section: Characterizationmentioning
confidence: 99%